Inter-port interactions in the Le Havre-Hamburg range: A scenario analysis using a nonautonomous Lotka Volterra model. (May 2018) - Marasco, Addolorata; Romano, Alessandro
Abstract: We propose an integrable nonautonomous Lotka-Volterra model to carry out a quantitative study of the interaction among container ports located in the Le Havre-Hamburg range. We find that mutualism is emerging among the ports located in the Benelux area, but not among German ports. Moreover, we develop three alternative scenarios and find that ( i ) for mutualism to emerge no port must be too strong vis-à-vis the others; ( ii ) the kind of interaction among ports depends on their geographic location, the services they provide, and demand-side factors; and ( iii ) upgrading intermodal connections can produce externalities that are not internalized by the investing port/country. Highlights: We propose a nonautonomous Lotka-Volterra model to study the interaction among the ports in the Le Havre–Hamburg range We connect the Lotka-Volterra models to the logit model We find that ports engage in nuanced interactions that go beyond pure competition We study the impact of the new extended gate service from Bruges-Zeebrugge to Antwerp on the interaction among the ports We develop three scenarios to study how changes in intermodal connections affect inter-port dynamics